Comparative study between uses of GnRH- agonist versus hCG as an ovulation trigger in patients with polycystic ovary syndrome in antagonist protocol - Nadkarni, Poornima; Nadkarni, Kishor; Nadkarni, Pooja; Singh, Prabhakar; Bhandal, Mandeep; Iche, Aditi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Polycystic ovary syndrome is one of the major causes of infertility. Almost 75% of ovulatory women have PCOS. Ovarian hyperstimulation syndrome and multiple pregnancies are known complications of PCOS in ART. Many studies are available now, to reduce the incidence and severity of OHSS in these patients, at the same time achieving acceptable pregnancy rate .In our study, we used Antagonist protocol in PCOS patients and compared the results using GnRH-Agonist versus hCG as ovulation trigger. Methods: This is double blinded comparative study between uses of GnRH- Agonist versus hCG as an ovulation trigger in 100 patients with polycystic ovary syndrome in antagonist protocol, done in private ART setting. In the study, 100 patients randomly allotted in two groups (A & B), each 50 patients, given ovulation trigger (When leading three follicles were >18 mm) as group A-GnRH-Agonist (Inj. Triptoreline 0.1 mg, 12 hours apart two doses subcutaneously) and group B hCG as (Inj. Recombinant hCG, 250 mcg single dose subcutaneously). Results: In our study, In 50 patients of group A, total 31 patients were pregnant. In group B of 50 cases, 29 patients were pregnant. There was no significant difference between two groups (P>0.05). Incidence of ovarian hyperstimulation syndrome is significantly less in PCOS patients, when GnRH agonist is used as ovulation trigger in Antagonist protocol, as compared to hCG (P <0.01).The incidence was mild OHSS was significantly(P<0.05) less in GnRH group. There was no significant difference in incidence of moderate OHSS (P>0.05). None patient of two groups developed severe OHSS. Conclusions: Incidence of the ovarian hyperstimulation syndrome is significantly less in patients with Polycystic Ovarian Syndrome when GnRH agonist is used as an ovulation trigger, as compared to hCG, in Antagonist protocol. In our study, there was no significant difference in pregnancy rates between two groups.